El concepto de cura según el curanderismo - Valdizán Montero, Gabriel (2022)
The present study seeks to describe the concept of cure from the “curanderil” tradition. An introduction to previous fundamental works is presented, as well as approaches to the concept of cure from different psychological perspectives. A series of interviews with “curanderos” were conducted to propose a cure based on the experience of convinced “curanderos”. Finally, different psychoanalytical proposals are presented regarding the findings.